A Descriptive Study of Registers Found in Spoken and Written Communication (A Semantic Analysis) - Nurul Hidayah (UIN Salatiga, 2009)
This research is descriptive study of registers found in spoken and written communication. The type of this research is Descriptive Qualitative Research. In this research, the data of the study is register in spoken and written communication that are found in a book entitled